2018
DOI: 10.1089/gtmb.2017.0281
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of Long Noncoding RNA IRAIN Is Associated with Poor Prognosis in Non-M3 Acute Myeloid Leukemia Patients

Abstract: Our finding suggests that IRAIN transcript levels may be a useful biomarker for the prognosis of non-M3 AML patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…The current results indicated that IRAIN expression was decreased in laryngeal carcinoma tissue, which is consistent with the findings of previous studies of AML (9,12), breast cancer (10) and renal cell carcinoma (30). However, the results are contrary to the findings of a study in NSCLC (11); this may be due to the fact that lncRNAs have tissue-specific expression patterns, which is different compared with the expression patterns of protein-coding genes (36,37).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current results indicated that IRAIN expression was decreased in laryngeal carcinoma tissue, which is consistent with the findings of previous studies of AML (9,12), breast cancer (10) and renal cell carcinoma (30). However, the results are contrary to the findings of a study in NSCLC (11); this may be due to the fact that lncRNAs have tissue-specific expression patterns, which is different compared with the expression patterns of protein-coding genes (36,37).…”
Section: Discussionsupporting
confidence: 93%
“…Another previous study reported that IRAIN was significantly increased in non-small cell lung carcinoma (NSCLC) tissues, was related to tumor size and smoking status and that downregulation of IRAIN suppressed the proliferation of NSCLC cells via blocking cells in G 1 phase ( 11 ). Pashaiefar et al demonstrated, in 64 de novo non-M3 patients with AML compared with 51 healthy controls that poor prognosis with low IRAIN expression tended to have a higher white blood cell count and blast count, and had markedly shorter overall survival (OS) and relapse-free survival (RFS; P=0.044 and 0.009, respectively); in addition, the study found that patients with a refractory response to chemotherapy and those with subsequent relapse, had lower initial IRAIN expression and multivariate analysis identified IRAIN transcript expression as an independent prognostic factor for OS and RFS ( 12 ). Previous studies have reported that the IGF1R pathway is frequently dysregulated in laryngeal carcinoma ( 8 , 13 ); however, it has not been determined whether IRAIN serves a role in laryngeal carcinoma.…”
Section: Introductionmentioning
confidence: 95%
“…Based on 64 de novo non-M3 AML patients, Pashaiefar et al found that low expression of IRAIN was independently associated with adverse prognosis: higher white blood cell count and blast counts and shorter OS and relapse-free survival. Besides, patients with refractory response to chemotherapies and those with subsequent relapse were more likely to show a lower initial IRAIN expression [183]. TUG1 has been in the spotlight of AML research.…”
Section: Prognostic Value Of Lncrnas In Acute Myeloid Leukemiamentioning
confidence: 99%
“…In this study, we show that lncRNA IRAIN was downregulated in RC cells and tissues, which was consistent with the results in RCC tissues and cells reported by Wang et al ( 25 ). Similarly, a study also showed downregulation of lncRNA IRAIN in non-M3 acute myeloid leukemia clinical specimens ( 26 ). Our data also demonstrated that lncRNA IRAIN downregulated VEGFA via recruitment of DNA methylation to the promoter region of VEGFA as evidenced by increased recruitment of Dnmt1, Dnmt3a, and Dnmt3b at the VEGFA promoter after overexpression of lncRNA IRAIN .…”
Section: Discussionmentioning
confidence: 87%